Anatomical recovery of the GABAergic system after a complete spinal cord injury in lampreys. (15th March 2018) - Romaus-Sanjurjo, D.; Valle-Maroto, S.M.; Barreiro-Iglesias, A.; Fernández-López, B.; Rodicio, M.C.
Abstract: Lampreys recover locomotion spontaneously several weeks after a complete spinal cord injury. Dysfunction of the GABAergic system following SCI has been reported in mammalian models. So, it is of great interest to understand how the GABAergic system of lampreys adapts to the post-injury situation and how this relates to spontaneous recovery. The spinal cord of lampreys contains 3 populations of GABAergic neurons and most of the GABAergic innervation of the spinal cord comes from these local cells. GABAB receptors are expressed in the spinal cord of lampreys and they play important roles in the control of locomotion. The aims of the present study were to quantify: 1) the changes in the number of GABAergic neurons and innervation of the spinal cord and 2) the changes in the expression of the gabab receptor subunits b1 and b2 in the spinal cord of the sea lamprey after SCI. We performed complete spinal cord transections at the level of the fifth gill of mature larval lampreys and GABA immunohistochemistry or gabab in situ hybridization experiments. Animals were analysed up to 10 weeks post-lesion (wpl), when behavioural analyses showed that they recovered normal appearing locomotion (stage 6 in the Ayer's scale of locomotor recovery). We observed a significant decrease in the number of GABA-ir cells and fibres 1 h after lesion both rostral and caudal to the lesion site. GABA-ir cell numbers and innervation were recovered to control levels 1 to 2 wpl. At 1, 4 and 10 wpl the expression of gabab1 and gabab2 transcripts was significantly decreased in the spinal cord compared to control un-lesioned animals. This is the first study reporting the quantitative long-term changes in the number of GABAergic cells and fibres and in the expression of gabab receptors in the spinal cord of any vertebrate following a traumatic SCI. Our results show that in lampreys there is a full recovery of the GABAergic neurons and a decrease in the expression of gabab receptors when functional recovery is achieved. Highlights: We analysed the recovery of the spinal GABAergic system after spinal cord injury in lampreys. There is an initial and acute loss of GABA immunoreactivity. The number of GABAergic cells and fibres is recovered completely between 1 and 2 weeks after the injury. The expression of the GABAB receptor was reduced even when the animals had recovered normal appearing locomotion.